THE IMPLEMENTATION OF SCIENTIFIC APPROACH OF THE 2013 CURRICULUM AT STATE JUNIOR HIGH SCHOOLS - Dara Novitasari; Ismail Petrus; Machdalena Vianty (University of Kuningan, 2022)
This study aims at reporting the results of a qualitative study investigating how English teachers implement the Scientific Approach (SA) in English teaching and learning at state junior high schools in Babat Toman. This study is particularly intended to answer three research questions: 1) How is scientific approach implemented in English teaching and learning at State Junior High Schools in Babat Toman, 2) What are the problems faced by the teachers in implementing scientific approach in English teaching and learning at state junior high schools in Babat Toman, and 3) What are the solutions to solve the problems in implementing scientific approach in English teaching and learning at state junior high schools in Babat Toman. The data were collected by using questionnaire, interview, observation, and document review. The participants of this study were the teachers of English, the vice-principal of curriculum, and the students. The findings of this study showed that the teachers used discovery learning to implement of scientific approach in the syntax of the learning model and five stages implemented in English teaching and learning. The problem faced by the teachers in implementing of scientific approach were, the students’ lack of critical thinking, the students’ difficulty in finding the answer of the problem, the students’ inability in analyzing the material, and the students’ lack of vocabulary mastery. The solutions used by the teachers to overcome the problem in applying Scientific Approach were: motivating the students to be more active in learning, giving some stimulates questions related to the material, comparing between the recent material and the previous materials, and translating the difficult words found by the students. The conclusion is the teachers had implemented scientific approach in the learning process.